Building trust in rural communities: recruitment and retention strategies in developmental science - Reck, Ava; Holley, Lauren; Bower, Kyle; Whitaker, Sarah; Hall, Caroline; Brown, Courtney; Berg, Alison; Alvarado, Caroline; Bales, Diane; Suma, Katharine; Fowler, Kimberly; Geier, Charles; et al. (Frontiers in Public Health, 2025)
BackgroundStudying human development often requires intimate interpersonal queries and interactions with children and families. Such research necessitates moving beyond traditional lab settings to engage participants within their communities for an extended period of time. Building trust is essential for conducting ecologically valid, longitudinal research, particularly when working with diverse and historically underserved populations. Developing effective, practical strategies to foster trust and rapport enhances recruitment, retention, and the overall quality of developmental research. This manuscript examines the recruitment and retention strategies aimed to facilitate trust and engagement in a longitudinal study involving rural participants in Northeast Georgia.MethodologyThe continuum of community engagement model suggests that research recruitment efforts should involve more than direct participant outreach, toward a multifaceted, community-driven approach. The current study employs a mixed-methods framework to evaluate these strategies in fostering trust and participant engagement. Qualitative data was collected from study reflection notes, interviews with extension agents, and participant surveys, alongside quantitative measures tracking enrollment, contacts, referrals, and participant trust.ResultsOur findings suggest that trust-building efforts, including community engagement teams, reciprocal community relationships, family and family-centered environments, and tailored communication strategies, enhanced participant engagement. Referrals emerged as the most effective method for recruitment. Integrating community-driven recruitment methods led to increased referrals and fostered long-term relationships and trust with community partners, but this success was only achieved after establishing connections and building trust within the community.ConclusionAddressing historical mistrust and promoting research inclusivity requires iterative, community-centered approaches. Our study highlights the importance of transparent communication, adaptive recruitment strategies, and sustained community engagement. Findings provide a framework for future research aiming to enhance trust, recruitment, and retention in complex biomedical and behavioral developmental science, ensuring more representative and impactful studies.